Association between exposure to urban waste and emotional and behavioral difficulties in schoolchildren - Tiago Sacchet Dumcke; Alais Benedetti; Luciano da Silva Selistre; Ana Maria Paim Camardelo; Emerson Rodrigues da Silva (Brazilian Society of Pediatrics, 2020)
Objective: To evaluate the association between living near waste recycling sites and emotional or behavioral difficulties in schoolchildren. Methodology: A cross‐sectional study with schoolchildren aged 6-13 years old from disadvantaged communities in a Brazilian city, divided between those who live less than 100 m away from the central point of the recycling site and those that live more than 150 m away from the site, as a control group and classified through georeferencing. The emotional and behavioral difficulties were investigated using the Strengths and Difficulties Questionnaire tool. Other variables were analyzed through logistic regression to determine their contribution to the outcomes. Results: Children living near waste recycling sites had a higher prevalence of emotional and behavioral problems than children living farther away. In the logistic regression model, no other covariates had a significant impact on the results, except for attending preschool. As expected, the families of the exposed group had lower income and lower levels of schooling, thus being characterized as a highly vulnerable population. Conclusion: The association between living near waste recycling sites and lower test performance raises concerns about the impact of inappropriate waste management in urban centers on children's health. Resumo: Objetivo: Avaliar a associação entre habitar próximo a sítios de reciclagem e dificuldades emocionais ou comportamentais em escolares. Metodologia: Estudo transversal com escolares de 6 a 13 anos de comunidades desfavorecidas em uma cidade do Brasil, divididas entre aquelas que tem sua residência situada a menos de 100 metros de distância do ponto central do sítio de reciclagem e aquelas que habitam a mais de 150 metros, como grupo controle e classificadas através de georeferenciamento. As dificuldades emocionais e comportamentais foram investigadas através do instrumento Questionário de Capacidades e Dificuldades. Outras variáveis foram analisadas através de regressão logística para determinar sua contribuição para os desfechos. Resultados: Crianças que vivem próximas a locais de reciclagem de resíduos tiveram maior prevalência de problemas emocionais e comportamentais do que as crianças que vivem mais afastadas. No modelo de regressão logística, nenhuma outra covariável apresentou impacto significativo sobre os resultados, à exceção de haver frequentado pré‐escola. Como esperado, as famílias do grupo exposto apresentaram menor renda e menores níveis de escolaridade, caracterizando‐se como uma população altamente vulnerável. Conclusão: A associação entre a habitação próxima a locais de reciclagem e um menor desempenho nos testes levanta preocupações sobre o impacto do manejo inadequado de resíduos nos centros urbanos sobre a saúde das crianças.